Ionic liquids toxicity on fresh water microalgae, Scenedesmus quadricauda, Chlorella vulgaris & Botryococcus braunii; selection criterion for use in a two-phase partitioning bioreactor (TPPBR) - Quraish, K.S. (Elsevier Ltd, 2017)
A promising method of Carbon dioxide (CO2) valorization is to use green microalgae photosynthesis to process biofuel. Two Phase Partitioning Bioreactors (TPPBR) offer the possibility to use non-aqueous phase liquids (NAPL) to enhance CO2 solubility; thus making CO2 available to maximize algae growth. This requires relatively less toxic hydrophobic Ionic Liquids (ILs) that comprise a new class of ionic compounds with remarkable physicochemical properties and thus qualifies them as NAPL candidates. This paper concerns the synthesis of ILs with octyl and butyl chains as well as different cations containing aromatic (imidazolium, pyridinium) and non-aromatic (piperidinum, pyrrolidinium) rings for CO2 absorption studies. The authors measured their respective toxicity levels on microalgae species, specifically, Scenedesmus quadricauda, Chlorella vulgaris and Botryococcus braunii. Results revealed that octyl-based ILs were more toxic than butyl-based analogues. Such was the case for bmim-PF6 at double saturation with an absorbance of 0.11, compared to Omim-PF6 at 0.17, bmim-NTf2 at 0.02, and Omim-NTf2 at 0.14, respectively. CO2 uptake results for ILs bearing octyl-based chains compared to the butyl analog were 54 (nCO2/nIL) (i.e., moles of CO2 moles of IL) and 38 (nCO2/nIL), respectively. Conclusively, 1-butyl-1-methylpiperidinium absorbed 13 (nCO2/nIL) and appeared the least toxic, having an absorbance of 0.25 at 688 nm (double saturation at 7 d) compared to 1-butyl-3-methylimidazolium, which showed the highest toxicity with zero absorbance. Accordingly, these findings suggest that 1-butyl-1-methylpiperidinium is capable of transporting CO2 to a system containing green microalgae without causing significant harm; thus allowing its use in TPPBR technology. © 2017 Elsevier Ltd